Develop planning indicators to activate the role of The National Labor Gateway ‘Taqat’ initiative to reduce unemployment in the Saudi society - Al Hamed, Reem Ibrahim (Journal of Humanities & Social Sciences, 2019)
This study aimed to develop planning indicators to activate the role of The National Labor Gateway ‘Taqat’ initiative to reduce unemployment in the Saudi society by identifying the role of Taqat initiative in reducing the phenomenon of unemployment, identifying the programs of Taqat initiative in reducing the phenomenon of unemployment, and identifying the obstacles facing Taqat initiative energies in reducing the phenomenon of unemployment. The study belonged to the descriptive analytical studies, and adopted the comprehensive social survey as its approach. The study sample consisted of all the beneficiaries of Taqat centers during the period of study application. The number of centers was (6): (2) for males and (4) for females. The researcher used the questionnaire tool to collect the data from the study sample.The number of study sample was (243) beneficiaries. The study reached a number of results; the most important results included the following: The Takat initiative has greatly increased the sense of national belonging, and the Takat initiative has contributed significantly to reducing the unemployment rate, and the desire of beneficies to join government positions has been one of the obstacles facing Takat. Based on this, a number of planning indicators were developed to activate the role of Taqat initiative in reducing unemployment, such as: Beneficiaries awareness, and try to change their attitudes towards work in the private sector. The social plan works to connect Taqat centers with the social development centers located in the districts.